Shell-inspired Ag3PO4-intercalated g-C3N4/GO heterostructure for integrated solar-driven desalination and photocatalytic water purification - Ruilai Liu; Junjie Pan; Yuhuan Su; Haitao Ye; Jinyun Zhao; Fangfang Wu; Yuping Wu; Jingbo Yang; Zongli Xie (Desalination, 2026)

Pore Structure Characteristics and Pore Structure-constrained Rock Physics Template-based Sweet Spot Evaluation Method for Tight Conglomerate Reservoirs - Peng Yang; Yihua Wen; Yadong Zhou; Yuping Su; Siyu Zhou; Gaojie Xiao; Yufeng Xiao; Yanfang Lü (Applied Geophysics, 2026)

Nitrogen enrichment alters the relationship between grassland biodiversity and ecosystem multifunctionality: A global meta-analysis - Tao Chang; Huakun Zhou; Hongye Su; Zeying Yao; Cuoji Peng; Hengkang Xu; Yuping Rong; Xinqing Shao (Agriculture, Ecosystems & Environment, 2026)

Numerical study on the thermal–hydraulic behaviors within a 19-pin wire-wrapped fuel assembly in lead-based fast reactors under porous blockage conditions based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Spatially resolved estimates of phytoplankton carbon fixation and diffusive methane flux potential in a subtropical reservoir - Sheraz Akhtar Gil; YuPing Su; Gohar Ayub; Abdul Samad; Muhammad Irfan Ahamad; Jehangir Ijaz; Shiyu Huang; Weng Yuxin (Environmental Monitoring and Assessment, 2026)

Multi-index remote sensing and GIS-based assessment of Shisper Glacier surge dynamics and glacial lake outburst flood hazard in Hunza, Pakistan - Maida Khanum; Yuping Su; Shakeel Mahmood; Kanwal Javid; Jehangir Ijaz; Sheraz Akhtar Gil; Muhammad Irfan Ahamad; Rana Muhammad Zulqarnain (Environmental Monitoring and Assessment, 2026)

Numerical study on the thermo-hydraulic behaviors of the Directionally-Alternated wire-wrapped fuel assembly in lead-cooled fast reactors based on SSTSAS k-ω-k-ε four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Nutrient input strategies mediate the link of rhizosphere soil microbiomes with rice productivity: Based on a decade-long field experiment - Ning Su; Xiangmin Rong; Qiaorong Li; Yansong Xiao; Guixian Xie; Chang Tian; Yali Kong; Yuping Zhang; Gongwen Luo (Agriculture, Ecosystems & Environment, 2026)

Numerical study on the turbulent heat transfer behaviors of the fuel assembly with spacer wires in lead-based fast reactors based on four-equation model - Yunxiang Li; Runsheng Yang; Yuefeng Guo; Xingkang Su; Yuping Zhou; Jian Hong; Yuxing Liu; Zinan Huang; Xin Su; Youpeng Zhang; WenJun Hu; Long Gu (Annals of Nuclear Energy, 2026)

Magma oxygen fugacity controls the mineralization of magmatic Cu-Ni sulfide deposits in orogenic belts: Insights from the Baixintan and Haibaotan intrusions, Eastern Tianshan, NW China - Tao Zheng; Yuping Su; Jianping Zheng; Jian Wang; Xin Li; Pengbing Li; Xiao Bian; Ke Geng; Xi Chen; Ying Wei (Lithos, 2026)

Achieving sustainable rice production with reduced nitrogen fertilization through unlocking soil organic nitrogen mineralization by alleviating microbial carbon limitation - Ning Su; Xiangmin Rong; Yao Liu; Junru Li; Runjia Yin; Guixian Xie; Yuping Zhang; Gongwen Luo (Field Crops Research, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

Health hazards associated with radon present in soil of Nizampur, Khyber Pakhtunkhwa, Pakistan - Jehangir Ijaz; Yuping Su; Nisar Ahmad; Muhammad Bakhsh (Isotopes in Environmental and Health Studies, 2026)

A comparative review of ecological models for freshwater ecosystems: frameworks, applications, and limitations - Sheraz Akhtar Gil; Yuping Su; Peng Diyi; Gohar Ayub; Guo Jing; Jehangir Ijaz; Tang Jian (Journal of Hydrology, 2026)

COMPASS: A multi-physics coupling platform for safety analysis of lead-cooled fast reactors - Zinan Huang; Yuxing Liu; You-Peng Zhang; Yunxiang Li; Wenjun Hu; Yuping Zhou; Jian Hong; Runsheng Yang; Xin Su (Annals of Nuclear Energy, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

Algae: A considerable regulator of methylmercury in mercury-contaminated paddy fields - Ling Su; Guangjun Luo; Tianrong He; Pan Wu; Ping Li; Deliang Yin; Yuping Xiang; Xian Zhou (Journal of Environmental Sciences, 2026)

Spatiotemporal Heterogeneity of Surface Evapotranspiration and its Driving Mechanisms in a Significant Ecological Recovery Area - Suhua Liu; Zhenfeng Zang; Xiangchao Qin; Xudong Huang; Chunying Wang; Hongbo Su; Yuping Han (Water Resources Management, 2025)

Histological studies on the ontogeny of the big-belly seahorse (Hippocampus abdominalis) - Yuanyuan Xue; Lu Tang; Chunhui Lv; Fang Wang; Xiaolei Su; Mingzhu Li; Yuping Hou; Jie Dong; Chengde Fan; Jiezhou Wang; Lin Shi; Qunhao Zhou; et al. (Fish Physiology and Biochemistry, 2025)

Remote sensing and in situ observations of harmful algal blooms in dongzhang reservoir: implications for water quality management - Muhammad Zahir; Yuping Su; Wang Xue; Sami Ur Rahman; Muhammad Imran Shahzad; Gohar Ayub (Environmental Geochemistry and Health, 2025)

Urban walkability assessment: methods and implications for city planning - Hamza Chaudhary; Shakeel Mahmood; Yuping Su; Muhammad Sajid Mehmood; Muhammad Irfan Ahamad (Environment, Development and Sustainability, 2025)

Selection and validation of reference genes for the normalization of RT-qPCR gene expression data in Rheum tanguticum (Polygonaceae) under various abiotic stresses - Mingjun Yu; Jiarui Jin; Xiaoli Li; Yuping Liu; Xu Su; Marcos A. Caraballo-Ortiz; Penghui Zhang; Qian Yang; Rongju Qu; Zhaxi Cairang; Xuanlin Gao; Yinghui Zheng (Journal of Plant Physiology, 2025)

Knowledge-based phosphorus input levels control the link between soil microbial diversity and ecosystem functions in paddy fields - Qiaorong Li; Yao Liu; Ning Su; Chang Tian; Yuping Zhang; Lin Tan; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

A review on monitoring, forecasting, and early warning of harmful algal bloom - Muhammad Zahir; Yuping Su; Muhammad Imran Shahzad; Gohar Ayub; Sami Ur Rahman; Jehangir Ijaz (Aquaculture, 2024)

Comparation of pheromone-binding proteins 1 and 2 of Spodoptera frugiperda in perceiving the three sex pheromone components Z9-14:Ac, Z7-12: Ac and Z11-16: Ac - Liming Hu; Taoli Zhang; Qingjun Wu; Kangyuan Liang; Guohui Yu; Muyang He; Dasong Chen; Xiangning Su; Yuping Zhang; Zhenfei Zhang; Jianmei Shen (Pesticide Biochemistry and Physiology, 2024)

Fault Interior Structure Index Construction and Quantitative Seismic Interpretation of Fault Facies - Yuping Su; Yan-fang Lyu; Feng Ma; Bin Zhang; Ming-xian Xie; Guang-po Chen (Applied Geophysics, 2024)

Li-mineralized pegmatite of anatectic origin: Constraints from Li Hf isotopes and geochemical modeling - Zhanlong Ma; Yong Tang; Yuping Su; Zhenghang Lv; Xin Zhang; Hui Zhang (Lithos, 2024)

Identification of carbonated eclogitic source for Cenozoic intraplate alkaline basalts from western Central Asia and its geodynamic implication - Tianyi Niu; Yuping Su; Jianping Zheng; Liang Zhou; Jian Wang; Xi Chen; Xiao Bian; Xiahui Zhang (Chemical Geology, 2024)

Anti-osteoporosis effect of Prunus humilis fruit on ovariectomized rats via modulating the function of bone metabolism - Xiaoying Wang; Yuping Sa; Chao Su; Lingling Yang; Weibiao Wang; Shuqin Ding; Wilson Gidion; Yue Zhang; Xueqin Ma (Food Bioscience, 2024)

The detoxification ability of sex-role reversed seahorses determines the sexual dimorphism in immune responses to benzo[a]pyrene exposure - Kai Wang; Yuanyuan Xue; Yali Liu; Xiaolei Su; Lei Wei; Chunhui Lv; Xu Zhang; Lele Zhang; Longwu Jia; Shiyi Zheng; Yicong Ma; Hansheng Yan; et al. (Science of The Total Environment, 2024)

Intraarticular botulinum toxin type A versus corticosteroid or hyaluronic acid for painful knee osteoarthritis: A meta-analysis of head-to-head randomized controlled trials - Yinan Yang; Guozheng Li; Yuping Su (Toxicon, 2024)

Origin and evolution of lithospheric mantle beneath the juvenile Arabian–Nubian Shield: Evidence from the Natash peridotite xenoliths, Southern Eastern Desert, Egypt - Xiao Bian; Yuping Su; Ezz El Din Abdel Hakim Khalaf; Jianping Zheng; Qing Xiong; Kai Xiong (Lithos, 2024)

Effectiveness of a 10-year continuous reduction of controlled-release nitrogen fertilizer on production, nitrogen loss and utilization of double-cropping rice - Ning Su; Xiangmin Ronga; Guixian Xie; Tian Chang; Yuping Zhang; Jianwei Peng; Gongwen Luo (Science of The Total Environment, 2024)

Environmental drivers and prediction of Karenia mikimotoi proliferation in coastal area, Southeast China - Jinzhu Su; Balaji Prasath Barathan; Yuping Su; Steve L. Morton; Chenxing She; Hong Zhang; Xiongsheng Lin (Marine Biology, 2024)

Considerable heating during clockwise decompression of a long-lived Paleoproterozoic hot orogen: Evidence from the Xuanhua Complex, North China Craton - Xiahui Zhang; Yuping Su; Jianping Zheng; Penglei Liu; Jian Wang; Liang Zhou (Precambrian Research, 2024)

Late Neoarchean and Paleoproterozoic tectonothermal and metamorphic evolution recorded in high-pressure granulites: Evidence from the Xuanhua Complex, northern North China Craton - Xiahui Zhang; Yuping Su; Jianping Zheng; Penglei Liu; Liang Zhou (Precambrian Research, 2023)

Enhanced effects of symbiosis between Tribonema sp. and aerobic denitrifying phosphorus accumulating bacteria on wastewater treatment and greenhouse gas reduction - Tongtong Xu; Wei Liu; Xuzhen Liu; Changsheng Zhao; Shuhao Huo; Fei Feng; Furen Guo; Xiaomeng Li; Xuan Cui; Yanyi Su; Yuping Yang (Journal of Environmental Chemical Engineering, 2023)

Circum-cratonic mantle archives the cumulative effects of plume and convergence events - Xiao Bian; Yuping Su; Jianping Zheng; Qing Xiong; Hongkun Dai; Xiang Zhou; Xi Chen; Liang Zhou; Jian Wang (Geochimica et Cosmochimica Acta, 2023)

The effects of nutrient loading from different sources on eutrophication in a large shallow lake in Southeast China - Balaji-Prasath Barathan; Wenting Chen; Yuping Su; Xue Wang; Yinxing Chen (Environmental Geochemistry and Health, 2023)

Constructing liquid metal/metal-organic framework nanohybrids with strong sonochemical energy storage performance for enhanced pollutants removal - Junjie Yan; Chen Su; Kequan Lou; Min Gu; Xinyu Wang; Donghui Pan; Lizhen Wang; Yuping Xu; Chongyang Chen; Yu Chen; Daozhen Chen; Min Yang (Journal of Hazardous Materials, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

PCDH8 protects MPP+-induced neuronal injury in SH-SY5Y cells by inhibiting MAPK pathway - Huaming Wei; Yuping Wu; Huanxia Zhuang; Hongyi Su (Molecular & Cellular Toxicology, 2023)

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

Effect of lossy thin-walled cylindrical food containers on microwave heating performance - Huacheng Zhu; Junhao Su; Fengming Yang; Yuping Wu; Jinghua Ye; Kama Huang; Yang Yang (Journal of Food Engineering, 2023)

Dissolved organic matter evolution can reflect the maturity of compost: Insight into common composting technology and material composition - Xiaoliang Kong; Gongwen Luo; Binghua Yan; Ning Su; Peng Zeng; Jialu Kang; Yuping Zhang; Guixian Xie (Journal of Environmental Management, 2023)

Characteristics of leachate from refuse transfer stations in rural China - Huiming Xiang; Le Cheng; Weiye Liu; Saier Wang; Yi Zhang; Lianghu Su; Chaoqun Tan; Yuping Li (Environmental Science and Pollution Research, 2023)

Effect of DAOA genetic variation on white matter alteration in corpus callosum in patients with first-episode schizophrenia - Wenjun Su; Tianyuan Zhu; Lihua Xu; Yanyan Wei; Botao Zeng; Tianhong Zhang; Huiru Cui; Junjie Wang; Yuping Jia; Jinhong Wang; Donald C. Goff; Yingying Tang; et al. (Brain Imaging and Behavior, 2021)

Coagulant Plus Bacillus nitratireducens Fermentation Broth Technique Provides a Rapid Algicidal Effect of Toxic Red Tide Dinoflagellate - Barathan Balaji Prasath; Ying Wang; Yuping Su; Wanning Zheng; Hong Lin; Hong Yang (Journal of Marine Science and Engineering, 2021)
When the toxic red tide alga Gymnodinium catenatum H.W. Graham accumulates in sediment through sexual reproduction, it provides the provenance of a periodic outbreak of red tide, a potential threat to the marine environment. In our study, the flocculation effects of four coagulants were compared. Bacteria fermentation (Ba3) broth and coagulant were combined with Ba3 to reduce the vegetative cells of G. catenatum, inhibit the cystic germination in the sediment, and control the red tide outbreak. To promote a more efficient and environmentally friendly algae suppression method, we studied these four coagulants combined with algae suppression bacteria for their effect on G. catenatum. The results show that polyaluminum chloride (PAC) is more efficient than other coagulants when used alone because it had a more substantial inhibitory effect. Ba3 broth also had a beneficial removal effect on the vegetative cells of G. catenatum. The inhibition efficiency of 2-day fermentation liquid was higher than that of 1-day and 3-day fermentation liquids. When combined, the PAC and Ba3 broth produced a pronounced algae inhibition effect that effectively hindered the germination of algae cysts. We conclude that this combination provides a scientific reference for the prevention and control of marine red tide. Our results suggest that designing environmentally friendly methods for the management of harmful algae is quite feasible.

Age-related compositional changes and correlations of gut microbiome, serum metabolome, and immune factor in rats - Xia Zhang; Yuping Yang; Juan Su; Xiaojiao Zheng; Chongchong Wang; Shaoqiu Chen; Jiajian Liu; Yingfang Lv; Shihao Fan; Aihua Zhao; Tianlu Chen; Wei Jia; et al. (GeroScience, 2021)

Early Mesozoic tectonic transition of the eastern South China Block: constraints from Late Triassic Dashuang complex in eastern Zhejiang Province - Xianbing Xu; Qiming Li; Lin Gui; Yuping Su; Xuefen Zhang (International Geology Review, 2019)

Characterization and phylogenetic analysis of the complete chloroplast genome of Orinus thoroldii (Poaceae) - Yuping Liu; Xu Su; Ting Lü; Tao Liu (Conservation Genetics Resources, 2018)

The complete chloroplast genome of Littledalea alaica (Korsh.) Petr. ex Nevski (Poaceae), an endemic species from the Qinghai-Tibetan Plateau - Xu Su; Yuping Liu; Ting Lü; Tao Liu; Di Zhu (Conservation Genetics Resources, 2018)

The complete chloroplast genome of Littledalea przevalskii Tzvelev (Poaceae: Bromeae), an endemic of the Qinghai–Tibetan Plateau - Ting Lü; Yuping Liu; Xu Su; Tao Liu; Di Zhu (Conservation Genetics Resources, 2018)

Characterization of the complete chloroplast genome sequence of Littledalea racemosa Keng (Poaceae: Bromeae) - Yuping Liu; Xu Su; Ting Lv; Tao Liu; Kelong Chen (Conservation Genetics Resources, 2018)

Effect of polysaccharides extracted from Sipunculus nudus (SNP) on the lifespan and immune damage repair of Drosophila melanogaster exposed to Cd (VI) - Jie Su; Linlin Jiang; Jingna Wu; Zhiyu Liu; Yuping Wu (Natural Product Research, 2018)

Comparative Pharmacokinetics of three major bioactive components in rats after oral administration of Typhae Pollen-Trogopterus Feces drug pair before and after compatibility - Huiting Zeng; Ping Xue; Shulan Su; Xiaochen Huang; Erxin Shang; Jianming Guo; Dawei Qian; Yuping Tang; Jin-ao Duan (DARU Journal of Pharmaceutical Sciences, 2016)

Effects of PAL and ICS on the production of total flavonoids, daidzein and puerarin in Pueraria thomsonii Benth. suspension cultures under low light stress - Hu Su; Hu Jiang; Yuping Li (Journal of Plant Biochemistry and Biotechnology, 2015)

Molecular cloning, expression pattern and phylogenetic analysis of the will die slowly gene from the Chinese oak silkworm, Antheraea pernyi - Yuping Li; Huan Wang; Runxi Xia; Song Wu; Shenglin Shi; Junfang Su; Yanqun Liu; Li Qin; ZhenDong Wang (Molecular Biology Reports, 2011)

Age, trace elements and Hf-isotope composition of zircon in eclogites from the sulu UHP belt, East-Central China: Neoproterozoic intrusion and subsequent Paleozoic and Early Mesozoic metamorphism - Jianping Zheng; Huayun Tang; Junhong Zhao; Yuping Su; Chunmei Yu; Qirong Wei; Qingsheng Liu; Xiuling Wu (Journal of Earth Science, 2010)

Integration of Double-Fluorescence Expression Vectors into Zebrafish Genome for the Selection of Site-Directed Knockout/Knockin - Yuping Wu; Guangxian Zhang; Qian Xiong; Fang Luo; Caimei Cui; Wei Hu; Yanhong Yu; Jin Su; Anlong Xu; Zuoyan Zhu (Marine Biotechnology, 2006)